Students' Perceptions of Learning Course Objectives: On Campus Versus Virtual Sections of One Course - Lori Cook-Benjamin (The Advocate, 2012)
The college course used in this project is required for students majoring in the Elementary Education and Early Childhood Unified Programs. Sections of the course are offered virtually as well as on the campus. This paper examines students' scores on an assignment called the Course Objective Reflection to determine if course format made a difference in the candidates' perceived learning of the six course objectives. Preliminary results indicate that virtual students achieved higher aggregate scores on the assignment than students completing the class on campus.